Apparent Colors of 2D Materials. Issue 4 (5th January 2022) - Puebla, Sergio; Li, Hai; Zhang, Hua; Castellanos-Gomez, Andres
Abstract : Finding 2D and thin‐film layered materials have become essential to develop not only in scientific‐related fields, but also in a wide industry, which is constantly feeding from this progress. For electronic devices, thin‐film materials are supposed to be a step forward to overcome Moore's law. In many other technologic areas, the development of tools based on flakes of materials has found new physics, becoming a rising field. Although, destructive techniques are commonly used to characterize the thickness of these materials. Herein, a list of materials is presented, whose thicknesses are characterized by their apparent colors in several substrates, a harmless, fast, and reliable technique that has been already used to determine the number of layers in several works. This list is also enlarged with other materials and substrates. Abstract : Finding thin films of layered materials has become essential for the development of several fields of research. Their qualitative colors, under optical microscope inspection, has become a widespread method to assess the thickness of the exfoliated materials. Herein the optical microscopy images of van der Waals materials to construct qualitative color charts to facilitate their rapid thickness estimation are summarized.